Composite material current collector, preparation method thereof and lithium metal battery

By designing a two-layer structure of composite current collectors, including a three-dimensional electrode structure and a dense electrode structure, the problem of high interface impedance between solid electrolyte and current collector in lithium metal batteries is solved, and the electrochemical performance and cyclic stability of the battery are significantly improved.

CN119315040AActive Publication Date: 2025-01-14TSINGHUA UNIVERSITY

Patent Information

Application Number
CN202411426930.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-14
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

The interface impedance between the solid electrolyte and the current collector in lithium metal batteries is high, which limits the discharge capacity and rate performance of the battery. The contact point between the solid electrolyte and the current collector is insufficient, affecting the electrochemical performance.

Method used

Design a composite current collector, adopts a double-layer structure of electrode three-dimensional structure and a dense electrode structure, including finger holes, mixes the current collector precursor and solid electrolyte material through ball milling method, and prepares it by double-layer scraping method and sintering process. A three-dimensional structure of solid electrolyte-current collector is formed to enhance the electrochemical reaction point of the electrode.

Benefits of technology

It effectively reduces the interface impedance between the solid electrolyte and the current collector, improves the discharge rate and cyclic stability of lithium metal batteries, improves the electrochemical performance, and significantly improves the discharge capacity and discharge power.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119315040A_ABST
    Figure CN119315040A_ABST
Patent Text Reader

Abstract

The invention relates to a composite material current collector, a preparation method thereof and a lithium metal battery. The composite material current collector comprises a current collector material and an optional solid electrolyte material, the composite material current collector is of a double-layer structure, one layer is of an electrode three-dimensional structure containing finger-shaped holes, and the other layer is of a compact electrode structure. A battery assembled by using the composite material current collector provided by the invention has more excellent electrochemical performance, and shows higher discharge capacity, higher discharge power and longer cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal lithium batteries and relates to a composite material current collector and a preparation method thereof and a lithium metal battery. Background Art

[0002] As the most widely used chemical energy device, lithium-ion batteries are limited by their theoretical energy density and can no longer meet the needs of social development for chemical energy devices. However, lithium metal batteries have the potential to replace lithium-ion batteries and become the next generation of major chemical energy devices due to their higher theoretical energy density, which is more than ten times that of lithium-ion batteries. Therefore, they have received extensive attention and research around the world.

[0003] The structure of lithium metal batteries includes positive electrode, negative electrode and electrolyte. The main difference between lithium metal batteries and lithium-ion batteries is that the active material of the negative electrode is lithium metal. Lithium metal batteries can be divided into water-based electrolyte lithium metal batteries, organic electrolyte lithium metal batteries and solid electrolyte lithium metal batteries according to the different electrolytes.

[0004] Although organic electrolyte lithium metal batteries have achieved some application results, the instability of organic electrolytes to metallic lithium has greatly limited the development of this electrolyte system, especially when the specific surface area of ​​the metallic lithium used is larger, the side reaction between the organic electrolyte and metallic lithium is more intense. At the same time, the evaporation and leakage of the electrolyte also have a negative impact on the safety of the battery. However, batteries using solid electrolyte systems can solve the above problems well.

[0005] The performance indicators of solid electrolytes in lithium metal batteries include lithium ion conductivity, physical stability when in contact with lithium metal, and chemical and electrochemical stability. Solid electrolytes that have been used in lithium metal batteries include polymer electrolytes and inorganic solid electrolytes. Among them, LLZTO in inorganic solid electrolytes has high lithium ion conductivity at room temperature and shows very high stability when in contact with lithium metal. However, the solid-solid contact between LLZTO and the current collector is poor, resulting in an increase in the interfacial impedance of the battery. At the same time, since the electrochemical reaction occurs at the three-phase interface of electrolyte-current collector-active material, the solid electrolyte LLZTO has insufficient contact points with the current collector, which limits the discharge capacity and rate performance of the battery.

[0006] CN117747928A discloses a solid electrolyte slurry, a composite current collector and a secondary battery, wherein a conductive agent, a lithium supplement, a solid electrolyte and an aqueous binder are simultaneously present in the solid electrolyte slurry, and p-hydroxyphenylacetamide is used as a dispersant, which has an excellent dispersing effect on each component. By applying the solid electrolyte slurry and water to the surface of the current collector, a composite current collector is obtained, and the internal resistance extreme fluctuation of the current collector is small, but the contact points between the current collector and the solid electrolyte are still limited, which limits the electrochemical performance of the battery.

[0007] Therefore, how to design a better lithium metal battery electrode, solve the interface problem between the electrolyte and the current collector, increase the reaction active sites, and improve the electrochemical performance of lithium metal batteries has become one of the current research focuses in this field. Summary of the invention

[0008] Problem that the invention aims to solve

[0009] The present invention aims to provide a composite material current collector and a preparation method thereof and a lithium metal battery, in particular a composite material current collector capable of reducing the interface impedance between the electrolyte and the current collector. The preparation method of the present invention can obtain a three-dimensional structure of the current collector (in particular a three-dimensional structure of a solid electrolyte-current collector integration), which increases the electrochemical reaction sites of the electrode, can improve the discharge rate and cycle stability of the electrode, and effectively reduce the interface contact impedance between the solid electrolyte and the current collector.

[0010] Solutions for solving problems

[0011] [1] A composite current collector, comprising a current collector material and an optional solid electrolyte material, wherein the composite current collector is a double-layer structure, wherein one layer is a three-dimensional electrode structure and the other layer is a dense electrode structure, wherein the three-dimensional electrode structure contains finger-like pores.

[0012] [2] The composite material current collector according to [1], wherein:

[0013] The current collector material is a negative electrode current collector material, preferably Cu, Ag or Ni;

[0014] The solid electrolyte material is an inorganic solid electrolyte or a polymer electrolyte, preferably a garnet solid electrolyte, more preferably LLZTO, LLZO or a mixture of the two.

[0015] [3] The composite current collector according to [1] or [2], wherein the average pore diameter of the finger-like pores is 5 to 80 μm, preferably 30 to 70 μm, and more preferably 40 to 50 μm.

[0016] [4] The composite material current collector according to any one of [1] to [3], wherein the overall thickness of the composite material current collector is 10 to 600 μm, preferably 100 to 500 μm, and more preferably 400 to 500 μm.

[0017] [5] The composite current collector according to any one of [1] to [4], wherein the thickness of the dense electrode structure is 2 to 400 μm, preferably 30 to 200 μm, and more preferably 40 to 60 μm.

[0018] [6] The method for preparing a composite material current collector according to any one of [1] to [5], comprising the following steps:

[0019] (1) using an oxide of a current collector material as a current collector precursor material, mixing the current collector precursor material and an optional solid electrolyte material, and ball milling the mixture to obtain a functional powder;

[0020] (2) mixing the solvent, the dispersant and the binder and subjecting them to ball milling to obtain a mixed solution;

[0021] (3) mixing the functional powder obtained in step (1) and the mixed solution obtained in step (2) and ball milling them to obtain slurry X;

[0022] (4) mixing carbon powder, solvent, dispersant and binder and ball milling to obtain slurry Y;

[0023] (5) using a double-layer scraping method, with slurry X on the upper layer and slurry Y on the lower layer, scraping on the surface of the thermoplastic polyester film tape to obtain an embryo body;

[0024] (6) placing the embryo obtained in step (5) into a flocculant to complete the exchange of the solvent and the flocculant in the embryo and the solidification of the embryo, and then drying;

[0025] (7) soaking the product obtained in step (6) in an alcohol solution of lithium chloride, washing away excess lithium chloride after soaking, and then drying;

[0026] (8) sintering the product obtained in step (7) in an air atmosphere to remove carbon powder, solvent, dispersant, adhesive and thermoplastic polyester film tape;

[0027] (9) placing the product obtained in step (8) in a sealed crucible in a lithium carbonate atmosphere for sintering;

[0028] (10) The product obtained in step (9) is subjected to reduction sintering using hydrogen to obtain a composite material current collector.

[0029] [7] The preparation method according to [6], wherein the mass ratio of the solid electrolyte material to the current collector precursor material is 0 to (3:1), preferably 0 to (2:1), and more preferably 1:9 to 1:1.

[0030] [8] The preparation method according to [6] or [7], wherein the current collector precursor material comprises at least two particles of different particle sizes;

[0031] Preferably, among the two particles of different particle sizes, the average particle size of the particles with a larger particle size is 1 to 20 μm, the particle size ratio of the particles with a larger particle size to the particles with a smaller particle size is 5:1 to 40:1, and the mass ratio is 0.1:1 to 3:1;

[0032] More preferably, among the two particles of different particle sizes, the average particle size of the larger particle size is 5 to 15 μm, the particle size ratio of the larger particle size to the smaller particle size is 10:1 to 30:1, and the mass ratio is 0.3:1 to 2:1.

[0033] [9] The preparation method according to any one of [6] to [8], wherein, if a solid electrolyte material is present, the solid electrolyte material comprises particles of at least two different particle sizes;

[0034] Preferably, among the two particles of different particle sizes, the average particle size of the particles with a larger particle size is 1 to 20 μm, the particle size ratio of the particles with a larger particle size to the particles with a smaller particle size is 5:1 to 40:1, and the mass ratio is 0.1:1 to 3:1;

[0035] More preferably, among the two particles of different particle sizes, the average particle size of the larger particle size is 5 to 15 μm, the particle size ratio of the larger particle size to the smaller particle size is 10:1 to 30:1, and the mass ratio is 0.3:1 to 2:1.

[0036]

[10] The preparation method according to [6] or [7], wherein, if a solid electrolyte material is present, the current collector precursor material and the solid electrolyte material are particles of two different particle sizes;

[0037] Preferably, among the two particles of different particle sizes, the average particle size of the particles with a larger particle size is 1 to 20 μm, the particle size ratio of the particles with a larger particle size to the particles with a smaller particle size is 5:1 to 40:1, and the mass ratio is 0.1:1 to 3:1;

[0038] More preferably, among the two particles of different particle sizes, the average particle size of the larger particle size is 5 to 15 μm, the particle size ratio of the larger particle size to the smaller particle size is 10:1 to 30:1, and the mass ratio is 0.3:1 to 2:1.

[0039]

[11] The preparation method according to [9], wherein in step (1), the functional powder comprises functional powder A and functional powder B; the preparation method of functional powder A is: mixing and ball-milling a solid electrolyte material with a large particle size and a current collector precursor material with a small particle size; the preparation method of functional powder B is: mixing and ball-milling a current collector precursor material with a large particle size and a solid electrolyte material with a small particle size.

[0040]

[12] The preparation method according to any one of [6] to

[11] , wherein

[0041] The carbon powder is graphite or carbon black;

[0042] The solvent is NMP or MBA;

[0043] The dispersant is PVP, PVA or CS;

[0044] The adhesive is PESf, PVDF or PAN;

[0045] The flocculant is water, ethanol or acetone.

[0046]

[13] The preparation method according to any one of [6] to

[12] , wherein

[0047] The drying temperature in step (6) is 60-80° C.

[0048] The drying temperature in step (7) is 60-80° C.

[0049] The sintering temperature in step (8) is 700-900°C;

[0050] The sintering temperature in step (9) is 800-1000° C.;

[0051] The sintering temperature in step (10) is 500-800°C.

[0052]

[14] A lithium metal battery comprising the composite material current collector described in any one of [1] to [5] or the composite material current collector obtained by the preparation method described in any one of [6] to

[13] .

[0053] Effects of the Invention

[0054] The present invention provides a composite current collector (such as a negative electrode current collector) with a specific structure and composition, which includes a current collector material and further includes a solid electrolyte. The composite current collector has a three-dimensional structure of finger-like holes of uniform size, has the function of current collector conductivity, further has the function of solid electrolyte ion conductivity, and has more electrochemical active sites between the current collector and the metal lithium, effectively improving the contact efficiency between the current collector and the solid electrolyte, and improving the discharge performance of the electrode.

[0055] The structure of the three-dimensional composite electrode with finger-shaped holes provided by the present invention can adjust the size and density of the finger-shaped holes in the structure, and the finger-shaped holes are axially perpendicular to the surface of the composite electrode, which is conducive to the active material metal lithium reaching the inside of the composite electrode. In addition, the close contact between the solid electrolyte and the current collector (such as the negative electrode current collector) forms a continuous ion transmission channel and an electron transmission channel, forming a large number of three-phase interfaces and active sites, which can improve the discharge capacity and discharge power of the lithium metal battery.

[0056] The experimental results show that the battery assembled using the composite material current collector provided by the present invention has more excellent electrochemical performance, showing higher discharge capacity, greater discharge power and longer cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0057] Figure 1 This is a flow chart for preparing the composite electrode (composite material current collector) of Example 1.

[0058] Figure 2 Schematic diagram of the mechanical ball milling coating process.

[0059] Figure 3 Schematic diagram of the double-layer scraping method.

[0060] Figure 4 The scanning electron microscope (SEM) observation results of the cross-sectional finger-like pore structure of the composite electrode prepared in Example 1.

[0061] Figure 5 This is the SEM observation result of the interface between the dense skin layer and the finger-like hole layer of the composite electrode prepared in Example 1.

[0062] Figure 6 This is the XRD spectrum of the composite electrode prepared in Example 1; wherein the upper spectrum is the XRD spectrum of the composite electrode, and * represents the three crystal planes of Cu; the lower spectrum is the standard card of LLZTO. DETAILED DESCRIPTION

[0063] Various exemplary embodiments, features and aspects of the present invention will be described in detail below. The word "exemplary" used here means "used as an example, embodiment or illustrative". Any embodiment described here as "exemplary" is not necessarily interpreted as being superior or better than other embodiments.

[0064] In addition, in order to better illustrate the present invention, numerous specific details are provided in the following specific embodiments. It should be understood by those skilled in the art that the present invention can be implemented without certain specific details. In other examples, methods, means, equipment and steps well known to those skilled in the art are not described in detail in order to highlight the subject matter of the present invention.

[0065] Unless otherwise stated, the units used in this specification are all international standard units, and the numerical values ​​and numerical ranges appearing in the present invention should be understood to include the inevitable systematic errors in industrial production.

[0066] In this specification, the word "may" means both performing a certain process and not performing a certain process.

[0067] In this specification, the references to "some specific / preferred embodiments", "other specific / preferred embodiments", "embodiments", etc., mean that the specific elements (e.g., features, structures, properties and / or characteristics) described in connection with the embodiments are included in at least one embodiment described herein, and may or may not exist in other embodiments. In addition, it should be understood that the elements may be combined in various embodiments in any suitable manner.

[0068] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints numerical values ​​A and B.

[0069] In the present specification, when "normal temperature" or "room temperature" is used, the temperature may be 15 to 30°C, further 15 to 25°C, for example, 20°C.

[0070] In the present invention, "composite current collector" is the same as "composite electrode".

[0071] In the present invention, "particle size" refers to an average particle size, and "particles having a larger particle size" refers to particles having a larger average particle size.

[0072] [Composite current collector]

[0073] The composite current collector provided by the present invention comprises a current collector material and an optional solid electrolyte material, wherein the composite current collector is a double-layer structure, wherein one layer is a three-dimensional electrode structure, and the other layer is a dense electrode structure, wherein the three-dimensional electrode structure contains finger-like holes. The double-layer structure of the composite current collector of the present invention can be clearly seen by SEM, as shown in the SEM photograph of the composite current collector obtained in Example 1. Figure 4 As shown, the upper layer is a three-dimensional electrode structure (containing a finger-like hole structure), and the lower layer is a dense electrode structure (also called a dense skin layer or a dense layer).

[0074] In the present invention, the components in the electrode three-dimensional structure and the dense electrode structure are the same, both are current collector materials and optional solid electrolyte materials. In some embodiments, the components in the electrode three-dimensional structure and the dense electrode structure are the same, both are current collector materials and solid electrolyte materials.

[0075] In some embodiments, the composite current collector provided by the present invention includes a current collector material and a solid electrolyte material.

[0076] In other embodiments, the composite current collector provided by the present invention includes a current collector material (i.e., does not include a solid electrolyte material). Experiments have shown that a composite current collector including a current collector material but not including a solid electrolyte material can also achieve better results, such as greater discharge power and longer cycle stability.

[0077] In some embodiments, the current collector material is a negative electrode current collector material, such as Cu, Ag, or Ni.

[0078] In some embodiments, the current collector material is a positive electrode current collector material, such as Al, Ag or Ni.

[0079] In some embodiments, the solid electrolyte material is an inorganic solid electrolyte or a polymer electrolyte, preferably a garnet-type solid electrolyte, such as LLZTO, LLZO or a mixture of the two.

[0080] In some specific embodiments, in the composite current collector of the present invention, the average pore size of the finger-like pores is 5 to 80 μm, preferably 30 to 70 μm, more preferably 40 to 50 μm, for example, 10 μm, 20 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 60 μm, 75 μm, etc.

[0081] In some specific embodiments, the overall thickness of the composite current collector of the present invention is 10 to 600 μm, preferably 100 to 500 μm, more preferably 400 to 500 μm, for example 50 μm, 100 μm, 200 μm, 250 μm, 300 μm, 350 μm, 450 μm, 550 μm, etc. In the present invention, "overall thickness" refers to the thickness of the overall structure of the composite current collector, that is, the thickness of the overall structure including the three-dimensional structure of the electrode and the dense electrode structure. In the present invention, the overall thickness of the composite current collector cannot be too thin. If it is too thin, the three-dimensional structure in the composite material cannot form enough reaction sites; at the same time, it cannot be too thick. If it is too thick, it is not conducive to the transmission of lithium ions away from the positive electrode.

[0082] In some specific embodiments, in the composite material current collector of the present invention, the thickness of the dense electrode structure is 2 to 400 μm, preferably 30 to 200 μm, and more preferably 40 to 60 μm, for example, 10 μm, 20 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 65 μm, 70 μm, 80 μm, 100 μm, 150 μm, 250 μm, etc.

[0083] [Method for preparing composite material current collector]

[0084] The present invention provides a method for preparing the composite material current collector, which comprises the following steps:

[0085] (1) using an oxide of a current collector material as a current collector precursor material, mixing the current collector precursor material and an optional solid electrolyte material, and ball milling the mixture to obtain a functional powder;

[0086] (2) mixing the solvent, the dispersant and the binder and subjecting them to ball milling to obtain a mixed solution;

[0087] (3) mixing the functional powder obtained in step (1) and the mixed solution obtained in step (2) and ball milling them to obtain slurry X;

[0088] (4) mixing carbon powder, solvent, dispersant and binder and ball milling to obtain slurry Y;

[0089] (5) using a double-layer scraping method, with slurry X on the upper layer and slurry Y on the lower layer, scraping on the surface of the thermoplastic polyester film tape to obtain an embryo body;

[0090] (6) placing the embryo obtained in step (5) into a flocculant to complete the exchange of the solvent and the flocculant in the embryo and the solidification of the embryo, and then drying;

[0091] (7) soaking the product obtained in step (6) in an alcohol solution of lithium chloride, washing away excess lithium chloride after soaking, and then drying;

[0092] (8) sintering the product obtained in step (7) in an air atmosphere to remove carbon powder, solvent, dispersant, adhesive and thermoplastic polyester film tape;

[0093] (9) placing the product obtained in step (8) in a sealed crucible in a lithium carbonate atmosphere for sintering;

[0094] (10) The product obtained in step (9) is subjected to reduction sintering using hydrogen to obtain a composite material current collector.

[0095] In some embodiments, when preparing the composite current collector of the present invention, an oxide of the current collector material is used as a current collector precursor material. In some embodiments, the current collector precursor material is a negative electrode current collector precursor material, such as CuO, Ag2O or NiO, and correspondingly, the composite current collector in the present invention can be used as a negative electrode current collector. However, the preparation method of the composite current collector of the present invention is also applicable to the preparation of the positive electrode current collector, and the current collector precursor material is replaced with a positive electrode current collector precursor material. In other embodiments, the current collector precursor material is a positive electrode current collector precursor material, such as Al2O3, NiO, Ag2O or Ag.

[0096] In some embodiments, the mass ratio of the solid electrolyte material to the current collector precursor material is 0 to (3:1), preferably 0 to (2:1), and more preferably 1:9 to 1:1. For example, the mass ratio may be 1:20, 1:10, 1:5, 1:2, 1.2:1, 1.5:1, etc.

[0097] In some embodiments, the current collector precursor material includes particles of at least two particle sizes, for example, particles of two particle sizes, ie, particles of a larger particle size and particles of a smaller particle size. In some preferred embodiments, among the particles of the two particle sizes, the average particle size of the larger particle size is 1 to 20 μm (preferably 5 to 15 μm, for example 8 μm, 10 μm, 12 μm, etc.), the particle size ratio of the larger particle size to the smaller particle size is 5:1 to 40:1 (preferably 10:1 to 30:1, for example 15:1, 20:1, 25:1, etc., and the specific values ​​may be: the larger particle size has an average particle size of 10 μm and the smaller particle size has an average particle size of 500 nm, the larger particle size has an average particle size of 5 μm and the smaller particle size has an average particle size of 500 nm, etc.), and the mass ratio is 0.1:1 to 3:1 (preferably 0.3:1 to 2:1, for example 0.4:1, 0.5:1, 0.8:1, 1:1, 1.5:1, etc.).

[0098] In some embodiments, a solid electrolyte material is present in the composite current collector, and the solid electrolyte material includes particles of at least two different particle sizes, for example, particles of two particle sizes, namely particles of a larger particle size and particles of a smaller particle size. In some preferred embodiments, among the particles of the two particle sizes, the average particle size of the larger particle size is 1 to 20 μm (preferably 5 to 15 μm, for example 8 μm, 10 μm, 12 μm, etc.), the particle size ratio of the larger particle size to the smaller particle size is 5:1 to 40:1 (preferably 10:1 to 30:1, for example 15:1, 20:1, 25:1, etc., and the specific values ​​may be: the larger particle size has an average particle size of 10 μm and the smaller particle size has an average particle size of 500 nm, the larger particle size has an average particle size of 5 μm and the smaller particle size has an average particle size of 500 nm, etc.), and the mass ratio is 0.1:1 to 3:1 (preferably 0.3:1 to 2:1, for example 0.4:1, 0.5:1, 0.8:1, 1:1, 1.5:1, etc.).

[0099] In some embodiments, the composite current collector contains a solid electrolyte material, that is, the composite current collector provided by the present invention includes a current collector material and a solid electrolyte material, and the current collector precursor material and the solid electrolyte material are particles of two different particle sizes, that is, particles of a larger particle size and particles of a smaller particle size. In this scheme, the particles of a larger particle size can be a current collector precursor material or a solid electrolyte material; the particles of a smaller particle size can be a solid electrolyte material or a current collector precursor material. In some preferred embodiments, among the particles of the two particle sizes, the average particle size of the larger particle size is 1 to 20 μm (preferably 5 to 15 μm, for example 8 μm, 10 μm, 12 μm, etc.), the particle size ratio of the larger particle size to the smaller particle size is 5:1 to 40:1 (preferably 10:1 to 30:1, for example 15:1, 20:1, 25:1, etc., and the specific values ​​may be: the larger particle size has an average particle size of 10 μm and the smaller particle size has an average particle size of 500 nm, the larger particle size has an average particle size of 5 μm and the smaller particle size has an average particle size of 500 nm, etc.), and the mass ratio is 0.1:1 to 3:1 (preferably 0.3:1 to 2:1, for example 0.4:1, 0.5:1, 0.8:1, 1:1, 1.5:1, etc.).

[0100] In some embodiments, in step (1), the solid electrolyte material includes at least two particles of different particle sizes, namely, a solid electrolyte material with a large particle size and a solid electrolyte material with a small particle size, and the current collector precursor material includes at least two particles of different particle sizes, namely, a current collector precursor material with a large particle size and a current collector precursor material with a small particle size.

[0101] In some preferred embodiments, in step (1), the functional powder comprises functional powder A and functional powder B; the preparation method of functional powder A is: mixing and ball-milling a solid electrolyte material with a large particle size and a current collector precursor material with a small particle size; the preparation method of functional powder B is: mixing and ball-milling a current collector precursor material with a large particle size and a solid electrolyte material with a small particle size.

[0102] In the preparation method of the present invention, all materials are mixed by ball milling (mechanical ball milling), and ultrasonic or stirring methods are not suitable for the present invention. First, the density of the materials in the present invention varies. If they are mixed by ultrasonic or stirring methods, the materials will subsequently settle, resulting in uneven material mixing. Secondly, in the preparation method of the present invention, there are more solid materials. After the solid and liquid materials are mixed, the resulting slurry is relatively viscous, and the use of ultrasonic or stirring methods will result in uneven material mixing. In addition, the ball milling method can coat the two particles. In the present invention, the mechanical ball milling coating process is shown in FIG. Figure 2Mechanical ball milling can be used to ball mill and coat particles (particles) of two different particle sizes to obtain mechanically coated particles in which coated particles (small particle size) coat main particles (large particle size). In some embodiments of the present invention, the functional powder comprises particles of two different particle sizes, and the particles of two different particle sizes can play a supporting role in the composite material current collector structure.

[0103] In the present invention, the rotation speed of the ball mill is not particularly limited, as long as the materials can be mixed evenly and fully coated. The rotation speed of the ball mill can be 100-500RPM, such as 200RPM, 300RPM, 400RPM, etc.

[0104] In the present invention, the ball milling time is not particularly limited as long as the materials can be evenly mixed and fully coated. The ball milling time can be 30 min to 48 h, for example, 30 min, 40 min, 1 h, 4 h, 8 h, 10 h, 20 h, 24 h, 30 h, 40 h, etc.

[0105] In some embodiments, the solvent used in the present invention may be NMP (N-methylpyrrolidone), MBA (N,N'-methylenebisacrylamide), or the like.

[0106] In some embodiments, the dispersant used in the present invention may be PVP (polyvinyl pyrrolidone), PVA (polyvinyl alcohol), CS (chitosan), and the like.

[0107] In some embodiments, the adhesive used in the present invention may be PESf (polyphenylene ether sulfone), PVDF (polyvinylidene fluoride), PAN (polyacrylonitrile), or the like.

[0108] In some embodiments, in step (2), the mass of the solvent is 0.5 to 2 times that of the functional powder in step (1), for example, 0.6 times, 0.7 times, 0.75 times, 0.8 times, 0.9 times, 1 times, 1.5 times, etc.

[0109] In some embodiments, in step (2), the mass of the dispersant is 0.01 to 0.2 times that of the functional powder in step (1), for example, 0.02 times, 0.03 times, 0.05 times, 0.08 times, 0.1 times, 0.12 times, 0.15 times, etc.

[0110] In some embodiments, in step (2), the mass of the adhesive is 0.01 to 0.5 times that of the functional powder in step (1), for example, 0.03 times, 0.05 times, 0.07 times, 0.09 times, 0.1 times, 0.15 times, 0.2 times, etc.

[0111] In the present invention, the type of carbon powder is not particularly limited, and any carbon powder is applicable to the present invention. In some embodiments, the carbon powder of the present invention may be graphite, carbon black, etc. In some embodiments, in step (4), the mass of the carbon powder is 0.1 to 2 times that of the functional powder in step (1), for example, 0.2 times, 0.3 times, 0.4 times, 0.6 times, 0.8 times, 1 times, 1.5 times, etc.

[0112] In some embodiments, in step (4), the mass of the solvent is 0.5 to 2 times that of the functional powder in step (1), for example, 0.6 times, 0.7 times, 0.75 times, 0.8 times, 0.9 times, 1 times, 1.5 times, etc.

[0113] In some embodiments, in step (4), the mass of the dispersant is 0.01 to 0.2 times that of the functional powder in step (1), for example, 0.02 times, 0.03 times, 0.05 times, 0.08 times, 0.1 times, 0.12 times, 0.15 times, etc.

[0114] In some embodiments, in step (4), the mass of the adhesive is 0.01 to 0.5 times that of the functional powder in step (1), for example, 0.03, 0.04, 0.05, 0.07, 0.09, 0.1, 0.15, 0.2, etc.

[0115] In the present invention, the size and density of the finger-shaped pores can be controlled by adjusting the ratio of the solvent, dispersant, and adhesive, that is, the process of phase transformation can be controlled. For example, compared with Example 1, increasing the ratio of the solvent, dispersant, and adhesive in Example 4 (compared with the functional powder) can significantly increase the pore size of the finger-shaped pores.

[0116] In some embodiments, in step (3) and step (4), it is necessary to degas slurry X and slurry Y. In some specific embodiments, slurry X and slurry Y can be degassed by vacuum degassing, for example, degassing in a vacuum oven; the degassing temperature can be 60 to 100°C, for example, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, etc.; the degassing time can be 40 to 70 minutes, for example, 40 minutes, 50 minutes, 60 minutes, etc.

[0117] In the present invention, a double-layer scraping method is used to evenly scrape the slurry X and the slurry Y on the surface of the thermoplastic polyester film. In some embodiments, in step (5), the thermoplastic polyester can be PET (polyethylene terephthalate), PBT (polybutylene terephthalate), etc. Figure 3 As shown, a scraper (scraper) is used with a double-layer scraper and a double-head casting mold to form an electrolyte-current collector precursor composite slurry (slurry X) on the upper layer and slurry Y (as shown in FIG. Figure 3The graphite slurry in the film is on the lower layer and the double layers are evenly scraped on the surface of the PET film.

[0118] In some embodiments, in step (5), the height of the double-layer scraper is 50 to 300 μm for the upper layer (e.g., 100 μm, 150 μm, 200 μm, 250 μm, 280 μm, etc.) and 360 to 600 μm for the lower layer (e.g., 400 μm, 450 μm, 500 μm, 550 μm, 580 μm, etc.).

[0119] In step (6) of the present invention, the embryo is placed in a flocculant to allow the solvent in the embryo to complete phase conversion with the flocculant. In some embodiments, the flocculant can be water, ethanol, acetone, etc. In some embodiments, the embryo is placed in the flocculant for 8 to 12 hours, such as 9 hours, 10 hours, 11 hours, etc.

[0120] In some embodiments, in step (6), the drying temperature is 60-80°C, such as 70°C, 75°C, 80°C, etc.; the drying time is 24-36h, such as 24h, 30h, etc.

[0121] In some embodiments, the soaking time of the alcohol solution of lithium chloride in step (7) is 0.5 to 1.5 hours, for example, 1 hour. In some specific embodiments, the mass concentration of the alcohol solution of lithium chloride can be 5% to 40%, for example, 8%, 10%, 15%, 20%, 30%, etc. In some specific embodiments, the alcohol in the alcohol solution of lithium chloride can be ethanol, methanol, n-propanol or isopropanol, etc.

[0122] In the present invention, the role of lithium chloride in step (7) is to provide a lithium environment for the product obtained in step (6), which can replenish lithium and prevent the loss of lithium.

[0123] In some embodiments, in step (7), after the soaking is completed, the excess lithium chloride can be washed away with ammonia water. In step (7), lithium chloride is selected for use. In addition to the above-mentioned functions, lithium chloride is also easy to remove. For example, ammonia water and excess lithium chloride can form ammonium chloride, which is decomposed by high temperature in subsequent steps to remove chloride ions without affecting the purity of the product.

[0124] In some embodiments, in step (7), the drying temperature is 60-80°C, such as 70°C, 75°C, 80°C, etc.; the drying time is 10-16h, such as 12h, 14h, etc.

[0125] In some embodiments, the sintering temperature in step (8) is 700-900° C., such as 750° C., 800° C., 850° C., 880° C., etc. The sintering time is 4-8 h, such as 5 h, 6 h, 7 h, etc.

[0126] In some embodiments, the sintering temperature in step (9) is 800-1000° C., such as 850° C., 900° C., 950° C., 990° C., etc. The sintering time is 2-4 h, such as 2 h, 3 h, 4 h, etc.

[0127] In the present invention, the role of lithium carbonate in step (9) is to provide a lithium environment for the product obtained in step (8), which can replenish lithium and prevent the loss of lithium. In addition to the above functions, the carbonate ions in lithium carbonate are also easily decomposed under high temperature conditions, so as not to affect the purity of the product.

[0128] In some embodiments, the sintering temperature in step (10) is 500-800° C., such as 600° C., 700° C., 750° C., 780° C., etc. The sintering time is 2-4 h, such as 2 h, 3 h, 4 h, etc.

[0129] In some embodiments, the temperature is lowered to room temperature after sintering in steps (8) to (10).

[0130] In some embodiments, the temperature may be increased by 2 to 3° C. / min, and the temperature may be decreased by 2 to 3° C. / min.

[0131] In some embodiments, the sintering in steps (8) to (10) can be performed in a muffle furnace.

[0132] In the present invention, the sintering in step (8) can oxidatively decompose the carbon powder, solvent, adhesive, dispersant, thermoplastic polyester film tape, etc., thereby removing the Y layer and the film tape, and the remaining X layer is then sintered in step (9) to obtain a double-layer structure containing a dense skin layer and a finger-shaped pore three-dimensional structure layer. The sintering in step (10) is carried out in a hydrogen atmosphere in order to reduce the current collector precursor material (i.e., the oxide of the current collector material, such as CuO) to the current collector material (i.e., a metal element, such as Cu). In some embodiments, the hydrogen atmosphere can be a pure hydrogen atmosphere or a mixed gas atmosphere of hydrogen and an inert gas. In some embodiments, the inert gas can be argon, helium, nitrogen, etc. In some embodiments, the volume fraction of hydrogen in the mixed gas of hydrogen and inert gas can be 2%-50%, for example, 5%, 10%, 15%, 20%, 30%, 40%, etc.

[0133] In the present invention, the composite layer structure of the X layer and the Y layer can prevent the current collector from breaking during the drying and sintering process, the Y layer can support the X layer, and the Y layer has a certain viscosity, which can make the X layer adhere to the surface of the Y layer well, and also ensure that the X layer can be evenly scraped on the surface of the Y layer. In addition, the Y layer can also control the depth of the phase transformation in the X layer, so that the finger-shaped holes will not penetrate the X layer, and a dense skin layer can be formed at the bottom of the X layer; if there is no Y layer, the finger-shaped holes will penetrate the X layer, and a dense skin layer cannot be formed.

[0134] [Lithium Metal Batteries]

[0135] In addition, the present invention also provides a lithium metal battery, which comprises the composite material current collector or the composite material current collector obtained by the above preparation method. In some specific embodiments, the lithium metal battery is assembled from the composite material current collector or the composite material current collector obtained by the above preparation method.

[0136] The preparation method of the lithium metal battery can be: assembling the composite material current collector, the insulating separator, and the lithium sheet, and depositing metallic lithium on the composite material current collector.

[0137] In some specific embodiments, an electrolyte is dripped into the insulating separator. The electrolyte may be a DME (ethylene glycol dimethyl ether) solution of LiTFSI, and the concentration may be 0.5 to 2 mol / L, for example, 1 mol / L.

[0138] In some specific embodiments, metallic lithium can be deposited on the composite material current collector by electrochemical deposition.

[0139] Example

[0140] The embodiments of the present invention will be described in detail below in conjunction with the examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0141] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention rather than limiting the patent claims of the present invention.

[0142] All raw materials of the present invention have no particular limitation on their sources, and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0143] There is no particular limitation on the purity of all raw materials in the present invention. The present invention preferably uses analytically pure materials or materials with conventional purity in the field of lithium metal batteries.

[0144] For further explanation, a composite material current collector and a preparation method thereof, and a lithium metal battery provided by the present invention are described in detail in combination with the following embodiments. However, it should be understood that these embodiments are implemented on the premise of the technical scheme of the present invention, and detailed implementation methods and specific operating processes are given only to further illustrate the features and advantages of the present invention, rather than to limit the claims of the present invention. The protection scope of the present invention is not limited to the following embodiments.

[0145] Example 1

[0146] This embodiment provides a three-dimensional structure composite material current collector (composite electrode) and a preparation method thereof, and a lithium metal battery, comprising the following steps:

[0147] S1. Preparation process of composite electrode (such as Figure 1 shown):

[0148] S1-1. Preparation of mixed powder for composite electrode: 1.5 g of LLZTO powder (i.e., large-particle electrolyte powder) with an average particle size of 10 μm and 13.5 g of CuO powder (i.e., small-particle current collector powder) with an average particle size of 500 nm were mixed and mechanically coated by ball milling (speed 300 RPM) for 40 min to obtain powder A; 13.5 g of CuO powder (i.e., large-particle current collector powder) with an average particle size of 10 μm and 1.5 g of LLZTO powder (i.e., small-particle electrolyte powder) with an average particle size of 500 nm were mixed and mechanically coated by ball milling (speed 300 RPM) for 40 min to obtain powder B;

[0149] S1-2. 22.75g solvent NMP, 2.73g binder PESf, 1.1g dispersant PVP were mixed and ball-milled (speed 300RPM) for 4h to obtain a mixed solution;

[0150] S1-3 Take 15g powder A, 15g powder B, add the above mixed solution, continue ball milling (speed 300RPM) 30h to obtain a uniform slurry X (ie, composite powder slurry);

[0151] S1-4. 9.87 g of graphite powder, 23.03 g of solvent NMP, 1.3 g of binder PESf, and 0.8 g of dispersant PVP were mixed and ball-milled (speed 300 RPM) for 24 h to obtain a uniform slurry Y (ie, carbon powder slurry);

[0152] S1-5. Put slurry X and slurry Y into a vacuum oven and degas at 80°C for 40 min; use a scraper and a double-headed scraper to apply a double-layer cast film of slurry X and slurry Y on a PET film tape, with film thicknesses of 300 μm and 600 μm, respectively;

[0153] S1-6. The scraped product (ie, composite powder / carbon powder double-layer green body) was quickly immersed in water as a flocculant for phase inversion and immersed for 10 hours; the product was taken out, dried at room temperature, placed in a vacuum oven, and dried at 80°C for 24 hours;

[0154] S1-7. The dried product was soaked in 40mL of 10% lithium chloride ethanol solution by mass for 1.5h, then rinsed with 25% ammonia water to remove excess lithium chloride, placed in an oven, and dried at 80°C for 12h;

[0155] S1-8. The dried product was placed in a muffle furnace, using an air atmosphere, and kept at 850 ° C for 6h for carbon removal (oxidative decomposition of carbon powder, solvent, adhesive, and dispersant), and then cooled to room temperature, with a heating and cooling rate of 3 ° C / min;

[0156] S1-9. The product after decarbonization is placed in a sealed crucible in a lithium carbonate atmosphere, and the sealed crucible is placed in a muffle furnace, and an air atmosphere is used to heat at 975 ° C for 3 hours for forming and sintering to sinter the composite powder to obtain a dense skin layer / finger-like hole double-layer structure, and then cooled to room temperature, and the temperature rise and fall rate is 3 ° C / min;

[0157] S1-10. Place the product in an atmosphere furnace, use a 5 volume % hydrogen-95 volume % argon atmosphere, keep the temperature at 750°C for 3 hours for reduction, so as to reduce the current collector powder to a metal element, and then cool it to room temperature at a heating and cooling rate of 3°C / min. Wash and dry the product to obtain an electrolyte-current collector composite electrode.

[0158] The composite electrode with a three-dimensional structure was taken out and subjected to SEM test. The observation results are shown in Figure 4 and Figure 5 , indicating that the composite electrode is a double-layer structure, that is, a three-dimensional electrode structure including finger-like pores and a dense electrode structure (dense layer), and the pore size of the finger-like pores is uniform. At this time, the overall thickness of the composite electrode is 433μm, the thickness of the dense layer is 58.8μm, and the average pore size of the finger-like pores is 44.1μm.

[0159] The composite electrode was subjected to XRD measurement as a whole. The results are shown in Figure 6 ,The results show that the composite electrode is composed of LLZTO and Cu with high purity.

[0160] S2. Preparation of lithium metal batteries:

[0161] S2-1. Assemble the composite electrode, the insulating separator and the lithium sheet into a battery in sequence, and deposit metallic lithium on the composite electrode by electrochemical deposition to obtain a lithium metal battery.

[0162] Example 2

[0163] The difference between this embodiment and embodiment 1 is that in step S1-1, a mixed powder for preparing a composite electrode is prepared: 7.5 g of LLZTO powder with an average particle size of 10 μm and 7.5 g of CuO powder with an average particle size of 500 nm are mixed and ball-milled for 40 minutes to obtain powder A; 7.5 g of CuO powder with an average particle size of 10 μm and 7.5 g of LLZTO powder with an average particle size of 500 nm are mixed and ball-milled for 40 minutes to obtain powder B.

[0164] The overall thickness of the obtained composite electrode is 429 μm, the thickness of the dense layer is 58.3 μm, and the average pore size of the finger-like pores is 47.5 μm.

[0165] Example 3

[0166] The difference between this embodiment and embodiment 1 is that in step S1-1, a mixed powder for preparing a composite electrode is prepared: 4.5 g of LLZTO powder with an average particle size of 10 μm and 10.5 g of CuO powder with an average particle size of 500 nm are mixed and ball-milled for 40 minutes to obtain powder A; 4.5 g of CuO powder with an average particle size of 10 μm and 10.5 g of LLZTO powder with an average particle size of 500 nm are mixed and ball-milled for 40 minutes to obtain powder B.

[0167] The overall thickness of the obtained composite electrode is 435 μm, the thickness of the dense layer is 57.2 μm, and the average pore diameter of the finger-like pores is 45.6 μm.

[0168] Example 4

[0169] The difference between this embodiment and embodiment 1 is that in step S1-1, a mixed powder for preparing a composite electrode is prepared by mixing 4.5 g of LLZTO powder with an average particle size of 10 μm and 10.5 g of CuO powder with an average particle size of 500 nm and ball-milling them for 40 minutes to obtain powder A, and powder B is not used.

[0170] The overall thickness of the obtained composite electrode is 430 μm, the thickness of the dense layer is 49.2 μm, and the average pore diameter of the finger-like pores is 60.8 μm.

[0171] Example 5

[0172] The difference between this embodiment and embodiment 1 is that the powder for preparing the electrode in step S1-1 does not contain a solid electrolyte component but only contains a current collector precursor component.

[0173] The overall thickness of the obtained electrode is 440 μm, the thickness of the dense layer is 47.8 μm, and the average pore diameter of the finger-like pores is 62.2 μm.

[0174] Example 6

[0175] The difference between this embodiment and embodiment 1 is that in step S1-1, a mixed powder for preparing a composite electrode is prepared by mixing and ball-milling 13.5 g of CuO powder with an average particle size of 500 nm (rotation speed 300 RPM) for 40 min to obtain powder A; and mixing and ball-milling 13.5 g of LLZTO powder with an average particle size of 500 nm (rotation speed 300 RPM) for 40 min to obtain powder B.

[0176] The overall thickness of the obtained composite electrode is 432 μm, the thickness of the dense layer is 48.8 μm, and the average pore diameter of the finger-like pores is 40.6 μm.

[0177] Comparative Example 1

[0178] The difference between this comparative example and Example 1 is that there is no step S1, and in step S2-1, copper foil is used instead of composite electrode to assemble the battery.

[0179] Performance Testing

[0180] The lithium metal batteries prepared in Examples 1 to 5 and Comparative Example 1 were subjected to rate charge and discharge tests, long cycle stability tests, and coulomb efficiency tests using a blue electric tester. The test rate of the battery was 0.5C to 8C (1C = 1 mA / cm 2 ), the test voltage range is -1 to 1V, and the cycle is 10 to 400 cycles. The test results are shown in Table 1. The cycle stability in Table 1 refers to the stability of the battery's charge and discharge voltage within the cycle. Beyond this cycle, the battery's charge and discharge voltage difference continues to increase, and the battery eventually fails.

[0181] Table 1 Performance test results of lithium metal batteries

[0182] Example / Comparative Example Rate performance (5 cycles) Coulombic efficiency maintained (≥97%) Cyclic stability Example 1 8C 88 cycles 289 cycles Example 2 4C 66 cycles 342 cycles Example 3 4C 63 cycles 134 cycles Example 4 4C 57 cycles 146 cycles Example 5 4C 46 cycles 225 cycles Example 6 4C 48 cycles 137 cycles Comparative Example 1 4C 10 cycles 134 cycles

[0183] The experimental results show that the discharge capacity of the battery assembled with the composite material current collector provided by the present invention (such as Example 1) can be increased to 2 times or more compared with the traditional current collector; the long-term cycle stability is significantly improved, and can even be increased to more than 2 times; the battery assembled with the composite material current collector provided by the present invention is cycled for more than 40 times (even more than 80 times), and the coulombic efficiency can still be maintained at more than 97%. It can be seen that the electrochemical performance of the battery assembled with the composite material current collector provided by the present invention is significantly improved compared with the battery assembled with the traditional current collector.

[0184] It should be noted that, although the technical solution of the present invention is introduced with specific examples, those skilled in the art will appreciate that the present invention should not be limited thereto.

[0185] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and variations will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or technical improvements in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.

Claims

1. A composite current collector, comprising a current collector material and an optional solid electrolyte material, wherein the composite current collector is a double-layer structure, wherein one layer is a three-dimensional electrode structure and the other layer is a dense electrode structure, wherein the three-dimensional electrode structure contains finger-like pores.

2. The composite current collector according to claim 1, characterized in that: The current collector material is a negative electrode current collector material, preferably Cu, Ag or Ni; The solid electrolyte material is an inorganic solid electrolyte or a polymer electrolyte, preferably a garnet solid electrolyte, more preferably LLZTO, LLZO or a mixture of the two.

3. The composite current collector according to claim 1 or 2, characterized in that: The average pore diameter of the finger-shaped pores is 5 to 80 μm, preferably 30 to 70 μm, and more preferably 40 to 50 μm.

4. The composite current collector according to any one of claims 1 to 3, characterized in that: The overall thickness of the composite material current collector is 10 to 600 μm, preferably 100 to 500 μm, and more preferably 400 to 500 μm.

5. The composite current collector according to any one of claims 1 to 4, characterized in that: The thickness of the dense electrode structure is 2 to 400 μm, preferably 30 to 200 μm, and more preferably 40 to 60 μm.

6. A method for preparing a composite material current collector according to any one of claims 1 to 5, comprising the following steps: (1) using an oxide of a current collector material as a current collector precursor material, mixing the current collector precursor material and an optional solid electrolyte material, and ball milling the mixture to obtain a functional powder; (2) mixing the solvent, the dispersant and the binder and subjecting them to ball milling to obtain a mixed solution; (3) mixing the functional powder obtained in step (1) and the mixed solution obtained in step (2) and ball milling them to obtain slurry X; (4) mixing carbon powder, solvent, dispersant and binder and ball milling to obtain slurry Y; (5) using a double-layer scraping method, with slurry X on the upper layer and slurry Y on the lower layer, scraping on the surface of the thermoplastic polyester film tape to obtain an embryo body; (6) placing the embryo obtained in step (5) into a flocculant to complete the exchange of the solvent and the flocculant in the embryo and the solidification of the embryo, and then drying; (7) soaking the product obtained in step (6) in an alcohol solution of lithium chloride, washing away excess lithium chloride after soaking, and then drying; (8) sintering the product obtained in step (7) in an air atmosphere to remove carbon powder, solvent, dispersant, adhesive and thermoplastic polyester film tape; (9) placing the product obtained in step (8) in a sealed crucible in a lithium carbonate atmosphere for sintering; (10) The product obtained in step (9) is subjected to reduction sintering using hydrogen to obtain a composite material current collector.

7. The preparation method according to claim 6, characterized in that: The mass ratio of the solid electrolyte material to the current collector precursor material is 0 to (3:1), preferably 0 to (2:1), and more preferably 1:9 to 1:

1.

8. The preparation method according to claim 6 or 7, characterized in that: The current collector precursor material includes at least two particles of different particle sizes; Preferably, among the two particles of different particle sizes, the average particle size of the particles with a larger particle size is 1 to 20 μm, the particle size ratio of the particles with a larger particle size to the particles with a smaller particle size is 5:1 to 40:1, and the mass ratio is 0.1:1 to 3:1; More preferably, among the two particles of different particle sizes, the average particle size of the larger particle size is 5 to 15 μm, the particle size ratio of the larger particle size to the smaller particle size is 10:1 to 30:1, and the mass ratio is 0.3:1 to 2:

1.

9. The preparation method according to any one of claims 6 to 8, characterized in that: If a solid electrolyte material is present, the solid electrolyte material comprises particles of at least two different particle sizes; Preferably, among the two particles of different particle sizes, the average particle size of the particles with a larger particle size is 1 to 20 μm, the particle size ratio of the particles with a larger particle size to the particles with a smaller particle size is 5:1 to 40:1, and the mass ratio is 0.1:1 to 3:1; More preferably, among the two particles of different particle sizes, the average particle size of the larger particle size is 5 to 15 μm, the particle size ratio of the larger particle size to the smaller particle size is 10:1 to 30:1, and the mass ratio is 0.3:1 to 2:

1.

10. The preparation method according to claim 6 or 7, characterized in that: If a solid electrolyte material is present, the current collector precursor material and the solid electrolyte material are particles of two different particle sizes; Preferably, among the two particles of different particle sizes, the average particle size of the particles with a larger particle size is 1 to 20 μm, the particle size ratio of the particles with a larger particle size to the particles with a smaller particle size is 5:1 to 40:1, and the mass ratio is 0.1:1 to 3:1; More preferably, among the two particles of different particle sizes, the average particle size of the larger particle size is 5 to 15 μm, the particle size ratio of the larger particle size to the smaller particle size is 10:1 to 30:1, and the mass ratio is 0.3:1 to 2:

1.

11. The preparation method according to claim 9, characterized in that: In step (1), the functional powder comprises functional powder A and functional powder B; the preparation method of functional powder A is: mixing and ball-milling a solid electrolyte material with a large particle size and a current collector precursor material with a small particle size; the preparation method of functional powder B is: mixing and ball-milling a current collector precursor material with a large particle size and a solid electrolyte material with a small particle size.

12. The preparation method according to any one of claims 6 to 11, characterized in that: The carbon powder is graphite or carbon black; The solvent is NMP or MBA; The dispersant is PVP, PVA or CS; The adhesive is PESf, PVDF or PAN; The flocculant is water, ethanol or acetone.

13. The preparation method according to any one of claims 6 to 12, characterized in that: The drying temperature in step (6) is 60-80° C. The drying temperature in step (7) is 60-80° C. The sintering temperature in step (8) is 700-900°C; The sintering temperature in step (9) is 800-1000° C.; The sintering temperature in step (10) is 500-800°C.

14. A lithium metal battery, comprising the composite material current collector according to any one of claims 1 to 5 or the composite material current collector obtained by the preparation method according to any one of claims 6 to 13.

Citation Information

Patent Citations

  • Three-dimensional mixed ion and electron conductor current collector as well as preparation method and application thereof

    CN108808008A

  • Three-dimensional porous current collector with gradient pore structure, and preparation method and application thereof

    CN112886021A

  • Integrated positive electrode, preparation method thereof and solid-state battery

    CN114079055A

  • Porous polyarylsulfone film composite copper foil and preparation method thereof

    CN117430863A

  • Solid electrolyte slurry, composite current collector and secondary battery

    CN117747928A

Cited By

  • Three-dimensional composite material current collector for lithium-containing battery, preparation method of three-dimensional composite material current collector, lithium metal battery and lithium air battery

    CN122025647A